Nephroblastoma of the Big Child, a Rare Entity: About a Case - Amine Cherraqi MD; Siham El Haddad PhD; Zaynab Iraqi Houssaini MD; Ola Messaoud MD; Rihane El Mohtarim MD; Najat Lamalmi PhD; Maria Elkababr PhD; Latifa Chat PhD; Nazik Allali PhD (SAGE Publishing, 2022)
Nephroblastoma is a renal blast tumor, the most common malignant renal tumor in children between 1 and 5 years of age. The average age of onset is 3.5 years, rarely occurring in children over 10 years of age. Its treatment is a model of medical-surgical collaboration. The prognostic factors are mainly the stage but recent studies have also shown that the advanced age of the child is a negative prognostic factor. We report a case of a 14-year-old child who presented with pain with swelling of the right hypochondrium, ultrasound showed a heterogeneous right retroperitoneal mass, MRI showed a large retroperitoneal tumor process with a right renal origin, in heterogeneous T2 signal, in T1 hyposignal, diffusion restricted, containing necrotic areas and heterogeneously enhancing after injection, responsible for pyelocalic dilatation and right renal venous thrombosis, extended to the IVC and the right atrium, with adenopathies, suggesting first a sarcoma. The extension workup showed pulmonary nodules of secondary appearance. An echo-guided biopsy was performed and the anatomopathological study confirmed the diagnosis of nephroblastoma.